2013
DOI: 10.6026/97320630009259
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis and phylogenetic study of some toxin proteins of snakes and related non-toxin proteins of chordates

Abstract: Snakes are equipped with their venomic armory to tackle different prey and predators in adverse natural world. The venomic composition of snakes is a mix of biologically active proteins and polypeptides. Among different components snake venom cytotoxins and short neurotoxin are non-enzymatic polypeptide candidates with in the venom. These two components structurally resembled to three-finger protein superfamily specific scaffold. Different non-toxin family members of three-finger protein superfamily are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For the translocation of BAX to mitochondria, a mitochondrial addressing signal of N-terminal Hα1 is believed to be necessary [29]. Recent bioinformatical research methods were very helpful for the discovery process of new biologically and biomedically important protein molecules [30][31][32][33][34][35][36][37][38][39]. Therefore, varied structural forms of BAX molecules in the different organisms (e.g., Chinese liver fluke) must be identified for bio-medical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…For the translocation of BAX to mitochondria, a mitochondrial addressing signal of N-terminal Hα1 is believed to be necessary [29]. Recent bioinformatical research methods were very helpful for the discovery process of new biologically and biomedically important protein molecules [30][31][32][33][34][35][36][37][38][39]. Therefore, varied structural forms of BAX molecules in the different organisms (e.g., Chinese liver fluke) must be identified for bio-medical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…science, pharmaceutical science, and biological science [10][11][12][13][14][15][16][17]. In recent years, literatures have reported that hesperetin possesses the potential to behave as an effective inhibitor of thrombin-like serine proteases isolated from the venom of Crotalus simus snakes [18].…”
Section: Panda and Ehsanmentioning
confidence: 99%
“…While planning, we have to take into consideration the strategies and experiences of other countries to circumvent costly errors and to revise the work in generating and managing the national health information system. Fortunately, recent state of the art informatics research practices makes it accomplishable to address tangled research problems in biomedical sciences [29][30][31][32][33][34][35][36].…”
Section: Health Information System: An Overviewmentioning
confidence: 99%